2005
DOI: 10.1016/j.jbankfin.2004.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Has competition in the Japanese banking sector improved?

Abstract: This paper investigates whether competition in the Japanese banking sector has improved in the last quarter of the 20th century. By estimating the first order condition of profit maximization, together with the cost function and the inverse demand function, we found that competition had improved, especially in the 1970s and in the first half of the 1980s. The results fail to reject a Cournot oligopoly for city banks for most of the period, while they do reject it for regional banks for the overall period. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 15 publications
6
77
0
1
Order By: Relevance
“…a reduction in competitive pressure) and efficiency. A well-known approach to measuring market power is suggested by Bresnahan (1982) and Lau (1982), recently used by Bikker (2003) and Uchida and Tsutsui (2005). They analyse bank behaviour on an aggregate level and estimate the average conjectural variation of banks.…”
Section: Measuring Competitionmentioning
confidence: 99%
“…a reduction in competitive pressure) and efficiency. A well-known approach to measuring market power is suggested by Bresnahan (1982) and Lau (1982), recently used by Bikker (2003) and Uchida and Tsutsui (2005). They analyse bank behaviour on an aggregate level and estimate the average conjectural variation of banks.…”
Section: Measuring Competitionmentioning
confidence: 99%
“…Uchida and Tsutsui (2005), using an approach similar to the one applied in this paper, considered the Japanese banking industry and estimated the degree of competition from 1974 to 2000. They found that the market had become more competitive in the 1970s, and judged that the city banks faced perfect competition in the middle of the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…To better infer the degree of bank competition, Uchida and Tsutsui (2005) is the first to modify the non-structural measure of competition derived from Bresnahan (1982) and applied to Japanese banks. The merit of this measure is that it does neither require any assumption on the equilibrium of the banking market as in Panzar and Rosse (1987), nor the market structure of each bank which can be different across banks, even for similar types of banks.…”
Section: Bank Market Structurementioning
confidence: 99%
“…The merit of this measure is that it does neither require any assumption on the equilibrium of the banking market as in Panzar and Rosse (1987), nor the market structure of each bank which can be different across banks, even for similar types of banks. Using a panel data methodology, Uchida and Tsutsui's (2005) method can again capture the degree of bank competition over time.…”
Section: Bank Market Structurementioning
confidence: 99%
See 1 more Smart Citation